Efektivitas Penerapan Kebijakan Dana Alokasi Khusus Subbidang Keluarga Berencana di Kabupaten Karimun (Policy Paper) - Denok Maya Dewi (Jurnal Ilmu Sosial dan Humaniora, 2023)
Dak it is to help the area, not replacing the APBD. For that it takes a strong commitment of district and city government to dak can be a lever for the region in achieving the objective set. This study aims to determine the effectiveness of the application of specialization of special allocation funds for the proud program of Kencana in Karimun District in 2022. The method used is descriptive qualitative with an inductive approach, that is describing the policy of special allocation funds (DAK) physical sub-field planning. Management and Implementation of Special Allocation Funds for Proud Programs Kencana After the Overall Menu / Details of the Overall Activities are well, but the current state conditions / conditions are conveniently to phase with a small pad, should be provided for the companion / supporting funds sourced from DAK.